2019
DOI: 10.1002/jcp.28121
|View full text |Cite
|
Sign up to set email alerts
|

Strong binding active constituents of phytochemical to BMPR1A promote bone regeneration: In vitro, in silico docking, and in vivo studies

Abstract: Two of the most problematic orthopedic and neurosurgeon visits are associated with spine and craniofacial fractures. Therefore, more attention needs to be paid to finding a medicine to repair these fractures. Amongst the most mysterious herbs, Aloe vera stands out. In the present study, the ameliorating function of A. vera on osteogenesis was studied in vitro and in vivo. Osteoblast‐like cells were exposed to A. vera, followed by analysis of cell viability, lactate dehydrogenase release, and intracellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…More precisely, the reaction derived from the pressure confinement of hydrogel produces a composite scaffold with more compressive strength. Our compressive strength results correspond with the study conducted by Saeedi et al, which demonstrated that, however, adding nominal amounts of dECM (up to 1.5% wt/vol) could not affect a statistically significant difference in mechanical features, its impact on cellular behavior is evident 46 . The mechanical characteristic of the resultant composite scaffold demonstrated that it might be a promising candidate in nasal cartilage regeneration since previous reports achieved nasal cartilage compressive modulus in the range of 0.9–2.7 MPa for the lateral and septal cartilage, respectively 1 , 52 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More precisely, the reaction derived from the pressure confinement of hydrogel produces a composite scaffold with more compressive strength. Our compressive strength results correspond with the study conducted by Saeedi et al, which demonstrated that, however, adding nominal amounts of dECM (up to 1.5% wt/vol) could not affect a statistically significant difference in mechanical features, its impact on cellular behavior is evident 46 . The mechanical characteristic of the resultant composite scaffold demonstrated that it might be a promising candidate in nasal cartilage regeneration since previous reports achieved nasal cartilage compressive modulus in the range of 0.9–2.7 MPa for the lateral and septal cartilage, respectively 1 , 52 .…”
Section: Discussionsupporting
confidence: 91%
“…The cDNA was used for 45 cycle PCR in a Rotor‐Gene Q real‐time analyzer (Corbett, Mortlake, Australia) using Eva Green master mix. Each sample was replicated three times 46 . The method of 2 −(ΔΔCT) was used to calculate the expression level of each gene, with beta Actin (β‐actin) as a reference gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation